Matching Heterogeneous Agents with a Linear Search Technology - Georg Nöldeke; Thomas Tröger (University of Bonn, Bonn Graduate School of Economics (BGSE), 2009)
Steady state equilibria in heterogeneous agent matching models with search frictions have been shown to exist in Shimer and Smith (2000) under the assumption of a quadratic search technology. We extend their analysis to the commonly investigated linear search technology.
Keywords: C78; D83; 330; Search; Matching; Steady State Equilibrium; Suchtheorie; Matching; Stationäre Volkswirtschaft; Theorie